EU membership conditionality in promoting acceptance of peremptory human rights norms: a case study in Albania considering public opinion. Issue 10 (26th November 2018) - Peshkopia, Ridvan; Konjufca, Drin; Salihu, Erblin; Lika, Jonida
ABSTRACT: Since its inception, European Union membership conditionality has played a major role in bringing EU candidate countries from former communist Eastern Europe in line with international human rights norms. In spite of such progress, those societies harbour significant inconsistencies in both their perception of what constitutes human rights and the role public trust in domestic and international actors plays in those perceptions. By highlighting those inconsistencies and discussing their origins, this paper aims at filling an explanatory gap related to instances when we should expect that EU membership conditionality would serve as an agent of human rights jus cogens, and when it would fail to do so. By relying on a probability simple random sample of public opinion data that we collected in Albania in 2016, we test our propositions with the case of people's support for ethnic minority rights, homosexual rights, Syrian refugees seeking women rights, asylum in Albania, and the reinstatement of the death penalty.